- TINDAKAN MENGHAMBAT MASUK (BARRIER TO ENTRY) PELAKU USAHA DALAM PERSPEKTIF HUKUM PERSAINGAN USAHA: - - Raafid Haidar Herfian; Anna Maria Tri Anggraini (Reformasi Hukum Trisakti, 2023)
The act of inhibiting and/or blocking entry is contained in Article (17), (19), and (25) of Law Number 5 Year 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition. Barrier to entry result in the difficulty for Business Actors to be participate in the market. The problem is how the qualifications of business actors' actions can be categorized as barriers to entry based on competition law and how the KPPU applies the element of barrier to entry in KPPU’s case. This research is a normative research that uses secondary data and is supported by interviews. The data is analyzed qualitatively and concluded by deductive method. The results of the research and analysis show that barriers to entry can occur due to the behavior of incumbent business actors and/or regulations that makes difficult for new players to enter. The forms of barrier to entry in KPPU decisions are the establishment of internal office memos containing requirements not to sell competitors' products, and setting high tariffs that burden competitors' production costs. Therefore, KPPU needs to clarify the term barrier to entry in its guidelines, and business actors should develop compliance guidelines to prevent violations of Law Number 5/1999